New species and records of Corydalidae (Insecta: Megaloptera) from Myanmar - Liu, Xingyue; Dvorak, Libor (Zootaxa, 2017)
Seven species of the family Corydalidae (Insecta: Megaloptera) are newly recorded from Myanmar, including a new species of the dobsonfly genus Protohermes van der Weele, 1907, P. burmanus sp. nov. A total of 18 species of Megaloptera are now known from Myanmar.